2010
DOI: 10.1016/j.jcat.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Relating methanol oxidation to the structure of ceria-supported vanadia monolayer catalysts

Abstract: Abstract.Vanadia "monolayer"-type catalysts supported on reducible oxides such as ceria previously have shown high activity for the selective oxidation of alcohols. Here, a model system consisting of vanadia particles deposited on well-ordered CeO 2 (111) thin films has been employed. Scanning tunneling microscopy (STM), photoelectron spectroscopy (PES), and infrared reflection absorption spectroscopy (IRAS) were used to characterize the VO x /CeO 2 surface as a function of vanadia loading. The formation of is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 73 publications
(125 reference statements)
8
79
2
1
Order By: Relevance
“…For the low-coverage sample, two desorption peaks are observed (i.e., at 305 and 595 K). For the high-coverage sample, the high-temperature signal dominates the spectrum peaked at 575 K, which is close to that observed for CeO 2 (111) surfaces [19,25,26,31], and indicates that the ceria is becoming more "film-like" at high coverages. The supported nanoparticles also…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…For the low-coverage sample, two desorption peaks are observed (i.e., at 305 and 595 K). For the high-coverage sample, the high-temperature signal dominates the spectrum peaked at 575 K, which is close to that observed for CeO 2 (111) surfaces [19,25,26,31], and indicates that the ceria is becoming more "film-like" at high coverages. The supported nanoparticles also…”
Section: Resultssupporting
confidence: 79%
“…TPD spectra on the ordered CeO 2 (111) film showed FA desorption at 565 K (not shown here), which is in excellent agreement with that observed in our previous study [31], but considerably lower than that observed above on the ceria nanoparticles (575 -595 K, see Fig. 3).…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…We have reported TPD spectra of methanol on ceria supported vanadia have been reported as a function of vanadia coverage [2]. The pristine CeO 2 (1 1 1) surface of a film grown on Ru(0 0 0 1) shows a formaldehyde desorption signal at ∼565 K. In the presence of vanadia, the desorption peak shifts to ∼590 K. Note that in those experiments methanol was exposed to the sample at 300 K. As the coverage of vanadia increases, the integral intensity of the peak decreases and finally becomes negligible for the highest VO x coverage.…”
Section: Vo X Oxide Clusters Supported On Ceo 2 (1 1 1) For Methanol mentioning
confidence: 99%
“…For instance, cerium oxide and vanadium oxide are important in catalysis and different model systems have been created in both cases to tackle fundamental questions [33][34][35][36][37][38][39][40]. On one side, CeO x has the ability of easily interconvert the oxidation state of the Ce n+ centres, making the material an interesting candidate as a catalyst for hydrocarbon oxidation reactions.…”
Section: Application In Catalysismentioning
confidence: 99%